Veterinary Graduate and Postgraduate Studies. European Colleges. Continuing Education: Problems and Opportunities for Greece - KYRIAKIS (Σ. Κ. ΚΥΡΙΑΚΗΣ), S. C. (Journal of the Hellenic Veterinary Medical Society, 2017)
Veterinary medicine education has undergone substantial changes from a strong occupational oriented training towards training with much diversity in veterinary and life science areas. This evolution has been clearly dictated by the society since the Veterinarian became the expert not only in treating animals, but also in the prevention of animal diseases, in animal welfare, in public health by means of control of foodstuff of animal origin and of zoonotic type of diseases. The broader spectrum of tasks of the Veterinarianis reflected in the veterinary education and specialization